Microstructural evolution of Ti-added interstitial free steel in high strain deformation by hot torsion. Issue 1 (July 2015) - Gholizadeh, R; Shibata, A; Terada, D; Tsuji, N
Abstract: The dynamically evolved microstructure under high strain deformation condition does still have many debatable aspects, particularly in the case of easy-recovery metals like bcc-iron. In this research, microstructural evolution in high strain deformation by hot torsion of Ti-added interstitial free (IF) steel was systematically investigated. Torsion specimens were deformed up to an equivalent strain of ∼ 7 at different temperatures (650 °C - 850 °C) and strain rates (0.01 s -1 - 1.0 s -1 ), i.e., under various values of the Zener-Hollomon (Z) parameter. Immediately after the deformation, samples were water-quenched and microstructures were investigated by electron backscattering diffraction (EBSD) measurements and electron channelling contrast imaging (ECCI). Flow stress-strain curves of the IF steel under various deformation conditions showed typical flow curves of high stacking fault energy metals at low Z values, i.e., a peak stress followed by slight softening. On the other hand, under the high-Z deformation conditions, the specimens showed a larger stress drop after a certain amount of deformation. EBSD-based quantitative analysis was used to study the microstructural transition between high and low Z values. At low Z values, the occurrence of strain induced boundary migration (SIBM) as an initiation of dynamic recrystallization (DRX) was clearly observed. On the other hand, at high Z values, grain subdivision phenomena led to very fine and elongated structures.